TELE-ICU BERMANFAAT DALAM PENCAPAIAN PELAYANAN BERKUALITAS - Rizany, Ichsan; Hariyati, Rr Tutik Sri (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2017)
The incidence of mortality in ICU was still very high. Critical Patients in ICU required a complexcare. Conditions of complex care required the trained and competent nurses but deployment ofpersonnel was still a constraint. The Utilization of tele-ICU have an chance to reduce mortality inpatients. The purpose of this paper is to guide the use of Tele-ICU. The method used is literaturereview. Literature used from 2010 - 2017 such as journal and article. Tele-ICU is a technologyfacility that Provides long-range interactions by health workers to get the Data and conditions ofICU Patients Directly from the bedside. Communication in the tele-ICU is done through audioand video technology at the patient's bedside. Tele-ICU Provides a benefit to Patients, nurses anddoctors. Utilization of tele-ICU have a key role in optimizing the quality of nursing care receivedby Patients in accordance with the arrangements and the right destination. Utilization of teleICU needs the support of top managers. The managers must perform properly managementfunction to build a tele-ICU.